Police recruits' attitudes toward the death penalty in Trinidad and Tobago - Wallace, Wendell C. (International journal of law, crime and justice, 2024)
Knowledge, attitudes and beliefs of police officers are important in shaping public opinion on the death penalty. However, there is a paucity of research in the Caribbean on police officers’ attitudes towards the death penalty and thus insufficient police scholarship on this topical issue. More specifically, there is a noticeable sparseness of scholarship on the death penalty using police recruits as proxies for such studies. As a result of this lacuna, the current study examined attitudes of police recruits towards the death penalty using a mixed-method approach to gather data on attitudes towards the death penalty as well as alternatives to the death penalty. Questionnaires were distributed to one hundred and seven individuals undergoing police recruit training at the Police Academy in Trinidad and Tobago. The data were distilled by gender, education level, marital status, and age range to determine attitudes towards the death penalty among the recruit population. The findings revealed: (1) high levels of support for the death penalty, (2) the death penalty is the most appropriate sentence for persons found guilty of murder, and (3) life imprisonment without the possibility of parole as the best alternative sentencing option to the death penalty. Three themes (consistent application of the death penalty, life imprisonment without parole, and murder only) emanated from the qualitative component of the instrument and these are discussed.